Digital Content Marketing Design on The Social Media Account Instagram The Awan Villas, Bali in Increasing Brand Engagement - I Made Binar Baskara; Titien Damayanti; Nyoman Gede Dewa Rucika (Eduvest - Journal of Universal Studies, 2025)
This study explores digital content marketing strategies used by The Awan Villas, Bali, to enhance brand engagement on Instagram. The rapid evolution of social media as a marketing tool has transformed how businesses interact with customers. However, The Awan Villas faces challenges such as inconsistent content, lack of dedicated social media management, and low follower engagement. This research aims to analyze content marketing strategies, assess audience interaction, and propose effective marketing tactics to optimize brand engagement. The study employs a qualitative descriptive method, gathering primary data through interviews with marketing personnel and guests, and secondary data from content analysis of The Awan Villas’ Instagram activities. Findings indicate that strategic content planning, visual consistency, interactive engagement, and optimized posting schedules significantly enhance follower interactions and strengthen brand identity. The research concludes that effective social media marketing strategies, when well-executed, can increase consumer engagement and brand awareness, contributing to long-term business success in the hospitality industry.